Certificate presentation ceremony: qualifying examination for registration as practising pharmacists (peperiksaan kelayakan mengamal farmasi) / Syahida Fathiah Ahmad Kamal, Dr. Mahmathi Karuppannan and Zakiah Mohd Noordin - Ahmad Kamal, Syahida Fathiah; Karuppannan, Mahmathi; Mohd Noordin, Zakiah (Faculty of Pharmacy, 2023)
Pharmacy Board of Malaysia has determined that in order to be registered and practice as a pharmacist, pharmacy students are required to pass the qualifying examination. The examination aimed to assess candidates' knowledge and ability to apply Malaysia laws regulating the sale and supply of medicinal products from pharmacies including Poisons Act 1952, Sale of Drugs Act 1952, Control of Drugs and Cosmetics Regulations 1984, Registration of Pharmacists Act 1951 and Medicines (Advertisement and Sale) Act 1956. It is held three times a year and the third and fourth year pharmacy students from the Faculty of Pharmacy UiTM have attended the exam session on 23rd November 2022.